Dealing with complex contamination scenarios: using a multi-geochemical approach to assess environmental quality and identify pollution sources in a semi-arid estuary from Brazil - Souza, Ivanildo S.; Santos, Felipe R.; Martins, Davi A.; Morais, Pollyana C. V.; Gama, Allyne F.; Nascimento, Ronaldo F.; Cavalcante, Rivelino M.; Abessa, Denis M. S. [UNESP] (Springer Nature, 2022)
The Jundiaí-Potengi Estuary (EJP) is located on the semi-arid coast of northeastern Brazil and is influenced by multiple sources of contamination. The sediment quality of EJP was assessed by using a multi-geochemical approach during the dry and wet seasons. Sediments were analyzed for concentrations of nutrients, metals, polycyclic aromatic hydrocarbons (PAHs), pesticides, hormones (natural and synthetic), and sterols. The results were integrated by multivariate methods. The sediment was altered by the presence of contaminants from anthropogenic and natural sources. The middle and lower estuarine areas were considered more degraded in both seasons. In these regions, metals, hormones, sterols, and PAHs were found, indicating that these regions are severely affected by industrial, sanitary and aquaculture effluents, combustion of fossil fuels, and oil spills. The upstream region was contaminated by pesticides. The contamination pattern along the EJP shows the prevalence of local sources which continuously release the chemicals into the estuary. Worse conditions occurred during the rainy season, when the runoff from urban and rural areas is more intense and carries a greater load of contaminants to the EJP.
Keywords: Emerging organic contaminants; Molecular markers; Semi-arid estuary; Source apportionment; Synthetic chemicals